Hukum Islam dalam Sistem Politik Hukum: (Studi Deskriptif Sejarah Hukum Islam di Indonesia) - Indah Abbas (Al-Mizan (e-Journal), 2017)
This article discusses the history of the development of Islamic law in the legal political system in Indonesia. The problem discussed in this article is how the history of the phases of Islamic law in Indonesia and how the formation of Islamic law in the development of the political system in Indonesia. The results showed that: First, the history of the development of Islamic law in Indonesia, namely from the pre-colonial period of the Netherlands, the Dutch colonial period, the period of Japanese occupation, the period of parliamentary democracy, the old and new order periods, and the reform period; Second, the position of Islamic law in the development of national law in Indonesia plays an important role in the orderliness of the Indonesian people, especially Muslims and is used as material in the preparation of national law